Eficacia de la reeducación vocal en diez sesiones clínicas - Gutiérrez, Alba; Bielsa, María del Prado; Asensio, Carlos Félix (Revista de Investigación en Logopedia, 2012)
A vocal rehabilitation programme must be based on a functional diagnosis. The information provided by the stroboscope in this regards is of key importance because it helps to design a specific therapy program. A team formed by phoniatricians and speech and language therapists is also very relevant because the collaboration of these professionals increases the efficiency of the program and reduces the costs for the healthcare system. This study is conducted to verify the effectiveness of a rehabilitation program composed by 10 treatment sessions in which one phoniatricians and two speech and language therapists collaborate closely. An assessment pre-and post-treatment is carried out. Both subjective and objective measures are used: vocal comfort questionnaire, perceptual voice assessment and acoustic analysis. The results confirm the efficacy of the ten sessions program and support the collaborative work of professionals involved in voice treatment.